2017
DOI: 10.7555/jbr.31.20160151
|View full text |Cite
|
Sign up to set email alerts
|

Ginger extract attenuates ethanol-induced pulmonary histological changes and oxidative stress in rats

Abstract: Chronic ethanol consumption is associated with changes in the function and structure of the lungs. The aim of this study was to investigate the effect of chronic ethanol exposure on the lungs and whether ginger extract mitigated pulmonary abnormalities induced by ethanol in rats. Male Wistar rats were divided into the control group, the ethanol group, and the ethanol plus ginger extract group. Six weeks of ethanol treatment increased the proliferation of lung cells, and induced fibrosis, inflammation and leuko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The antioxidant effects of the active compounds of ginger, specifically gingerol and shogaol, on heart structure can also be seen through the inhibition of leukotriene and prostaglandin biosynthesis by suppressing 5-lipooxygenase synthetase [94]. This finding was similar to the finding from a study by Shirpoor et al [95], which showed that the lung abnormalities induced by oxidative stress can be improved by the antioxidant and anti-inflammatory properties of ginger.…”
Section: Ginger As An Antioxidant Involved In Delaying Ageingsupporting
confidence: 79%
“…The antioxidant effects of the active compounds of ginger, specifically gingerol and shogaol, on heart structure can also be seen through the inhibition of leukotriene and prostaglandin biosynthesis by suppressing 5-lipooxygenase synthetase [94]. This finding was similar to the finding from a study by Shirpoor et al [95], which showed that the lung abnormalities induced by oxidative stress can be improved by the antioxidant and anti-inflammatory properties of ginger.…”
Section: Ginger As An Antioxidant Involved In Delaying Ageingsupporting
confidence: 79%
“…Previous studies indicate that alcohol induced DNA damage and oxidative stress are associated with cancer risk, and promoted tumor metastasis [34][35][36]. According to epidemiological evidence, alcohol might play a causative role in developing oral cancer [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Ameliorative effects of H. sabdariffa on pulmonary fibrosis and chronic inflammatory interstitial lung disease have also been studied using rats exposed to a toxic chemical (Hemmeti et al 2016, Ajibade et al 2021. It has been demonstrated that pre-treatment using Z. officinale extract improves lung function and normalizes lung injuries in alcoholic humans and rats exposed to polychlorinated biphenyls (Alireza et al 2017, Ahd et al 2019. The administration of T. occidentalis extract to animals resulted in the repair of lung tissue damage.…”
Section: Discussionmentioning
confidence: 99%